2019
DOI: 10.1080/17453674.2019.1597062
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient survival following reoperation after total hip replacement and the reason for reoperation: an analysis of 9,926 patients in the Swedish Hip Arthroplasty Register

Abstract: Background and purpose — The association between long-term patient survival and elective primary total hip replacement (THR) has been described extensively. The long-term survival following reoperation of THR is less well understood. We investigated the relative survival of patients undergoing reoperation following elective THR and explored an association between the indication for the reoperation and relative survival. Patients and methods — In this observational cohort study we selected the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The treatment of PPFx has been associated with high risk of failure, poor outcomes and worst survival outcome compared to the general population 1 year after surgery. This still applies 5-8 years after the surgery [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of PPFx has been associated with high risk of failure, poor outcomes and worst survival outcome compared to the general population 1 year after surgery. This still applies 5-8 years after the surgery [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that undergoing revision surgery for periprosthetic fractures results in worse survival outcomes than the general population within 1 year, and this negative influence extends for several years after the surgery [ 10 ]. Non-operative management is usually not appropriate for the well-known complications produced by immobilization and for the high percentages of non-unions in fractures around a cemented stem [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Revision risk due to these causes is higher after uncemented THAs (Hailer et al 2010, Stea et al 2014, Dale et al 2019. Such complications may implicate a poorer functional outcome, increased morbidity, and long-term mortality (Lindahl et al 2007, Gundtoft et al 2017, Cnudde et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The exception was that uncemented THA in females over 55 years of age had a higher risk of revision due to aseptic loosening, periprosthetic fracture, and dislocation. Patients may have increased long-term mortality after such revisions (Gundtoft et al 2017, Cnudde et al 2019). 3-day and 10-year mortality was similar for all fixations in our study, indicating that perioperative-, short-term, or long-term mortality risk should not dictate what fixation principle to choose in primary THA, even in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cnudde et al [12] reported that the proportion of all-cemented implants decreased from 92% in 1999 to 68% in 2012. In 2019, Cnudde et al [16] retrospectively analyzed 9,926 patients from the SHAR who underwent revision THA and reported aseptic loosening as the leading cause of failure, followed by infection, periprosthetic fracture, and instability (3558, 2065, 1574, and 1782 cases, respectively). These data are of great bene t in improving patient clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%